1992
DOI: 10.1063/1.106495
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of porous silicon buried underneath epitaxial GaP

Abstract: Recent observations of visible, room-temperature photoluminescence in porous Si have stimulated research aimed at the realization of efficient, Si-based electroluminescent devices. To achieve electroluminescence, it may be beneficial to generate carriers with sufficient energy to populate the states of the quantum-confined Si structures. A viable method to accomplish this is to utilize a wide-band-gap heterojunction injector, such as GaP. Toward that end, we report the successful formation of porous Si buried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1992
1992
1997
1997

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…The light emission from Si is in the near infrared region and very inefficient (typically ~-10" 4 %). 4 This limits the applications of Si in optoelectronics where the direct gap III-V compounds, such as GaAs and InP, dominate. The discovery of the strong and visible RT photoluminescence and electroluminescence may result in the merger of optoelectronics and Si-based integrated processing techniques, and hence open a new field in optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…The light emission from Si is in the near infrared region and very inefficient (typically ~-10" 4 %). 4 This limits the applications of Si in optoelectronics where the direct gap III-V compounds, such as GaAs and InP, dominate. The discovery of the strong and visible RT photoluminescence and electroluminescence may result in the merger of optoelectronics and Si-based integrated processing techniques, and hence open a new field in optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Most of the studies reported so far have concentrated on photoluminescence (PL) properties of PS. [6][7][8][9][10][11] Electroluminescence (EL) is, however, more important as far as technological application is concerned. In this respect, Koshida and Koyama demonstrated that a transparent metal/PS/p-Si/Al cell emits EL (orange) with relatively low applied voltage, although the quantum efficiency was quite low (10 -5 %).…”
Section: Introductionmentioning
confidence: 99%
“…Este processo, aparentemente, forma fios quânticos autosustentados da ordem de 2 nanometros de espessura, tendo sua enorme luminescência explicada como resultante de efeitos de confinamento quântico [35]. Esta conclusão sobre a luminescência do silício poroso tem sido apoiada por diversos pesquisadores [36][37][38][39][40][41][42][43][44][45][46]. Modelos teóricos combinados com diversas técnicas espectroscópicas tem sido utilizados para buscar dar suporte a esta idéia [34,[47][48][49].…”
Section: A Origem Da Luminescência No Silício Porosounclassified